Reflections on the birth certificate in relation to the Pancharevo and Rzecznik cases - Campuzano Díaz, Beatriz (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
In the Pancharevo and Rzecznik cases, a problem arises regarding the birth certificate issued by the Spanish authorities with respect to minors, daughters of same-sex couples, born in our country. The considerations made by the CJEU in relation to the issuance of a new birth certificate or its registration in the Member State of which the mothers are nationals and the problems associated with the freedom of movement and residence, are analyzed in this work from the Spanish perspective. The novelties that the proposal for a regulation on parenthood may bring in relation to these issues are also raised.